Avison and his Subscribers: Musical Networking in Eighteenth-Century Britain. Issue 1 (2018) - Fleming, Simon D.I.
Abstract : One of the most important and valuable resources available to researchers of eighteenth-century social history are the lists of subscribers that were attached to a wide variety of publications. Yet, the study of this type of source material remains one of the areas most neglected by academics. These lists shed considerable light on the connections that an author or composer had with other like-minded individuals and the support that they received from members of the middle and upper classes. In cases where a single composer published a series of works by subscription, there is an opportunity to gain an insight into the growth of the public's appreciation of the composer and the contacts he or she forged over the course of a lifetime. Charles Avison is one of the best known British composers from the eighteenth century. He issued six works by subscription between 1740 and 1767 and they together provide a unique insight into his growth into one of this country's leading native musicians. Although a respectable number of the associations discussed are already known through other sources, this study not only reinforces the importance of these associations, but additionally gives an insight into those links for which there is no other known evidence. This research ultimately reveals that Avison's location in the North-East of England did not significantly impact on his ability to forge connections across Britain and beyond.